Determining EOQ Regarding the Quality of Products, Destructive Inspection, Reworking and a Review of Shortage and Deteriorating Items - Hassan Torabi; Mohammad Hossein karimi Gavareshki; Morteza Abbasi (مدیریت مهندسی و رایانش نرم)
Among the most important unrealistic assumptions of EOQ model is the perfect quality of items received in stock. Trying to overcome this constraint and making the mentioned model get closer to real circumstances, this paper considers destructive inspections and the existence of imperfect and rejected items after reworking.  EOQ is determined under three following conditions: 1- rejecting the imperfect and reworkable items after the inspection 2-keeping the aforementioned items until the end of the inspection period, and 3- keeping these items until the end of the cycle. Results show that using the traditional model instead of the modified new model will lead to increased costs. In other words, with an increase in total proportions of imperfect and reworkable items, EOQ and the total cost per unit of time will increase. A numerical example is solved to evaluate the results.